PRODUCTION OF DOCUMENTARY FILM DRIVING AWARENESS - Ranangsari, Kosalalita Anggiyumna; Fuquan, Qiu (Capture : Jurnal Seni Media Rekam, 2020)
The film "Driving Awareness" tells about the importance of driving according to the rules for mutual safety. This film uses a linear storyline and character flashback plot. The purpose of this paper is to describe the concept and visualization of the documentary film "Driving Awareness". The stages in designing the creation of the documentary film "Driving Awareness" start from the idea, preproduction, production, then post-production. In the idea stage, the idea of a film story is determined together with the team and then converted into a script for the film to be made into a storyboard to illustrate every scene in the film as well as a detailed storyline. The pre-production stage determines the position of each person in filmmaking, selecting players, determining locations, and scheduling filming activities. Production activities are carried out according to a predetermined schedule by recording images of each scene. The whole shot was edited to make a whole film work and add backsound, transition effects, and coloring.